The optimal coastal retracked sea levels from Saral/Altika satellite altimetry over the Southeast Asia - Noor Nabilah Abdullah, 1990-, author; Nurul Hazrina Idris, supervisor; Nurul Hawani Idris, 1981-, supervisor; Fakulti Geoinformasi dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Falsafah) - Universiti Teknologi Malaysia, 2018